Integrasi Supervisi Klinik Modern dan Nilai-Nilai Islam dalam Pembinaan Profesionalisme Guru - Jaswadi Jaswadi; Agus Zaenul Fitri (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study originates from the issue of low teacher professionalism in Islamic educational institutions, which is still dominated by administrative supervision practices that fail to address personal and spiritual development. In this context, Islamic value-based clinical supervision is proposed as an integrative approach to holistically enhance teacher professionalism. This research employs a library research method by reviewing academic literature such as books, journals, research reports, and scientific articles related to clinical supervision and teacher professionalism. Data were collected through the identification, selection, and analysis of relevant sources using content analysis techniques. The findings reveal that clinical supervision based on Islamic values not only strengthens teachers’ pedagogical and professional competencies but also fosters spiritual awareness through the principles of tazkiyah (self-purification) and islah (self-improvement). The main contribution of this study lies in integrating modern clinical supervision theory with transcendental Islamic values, thereby presenting a model of teacher development grounded in spirituality and professional ethics. These findings highlight the importance of implementing Islamic-based clinical supervision as a strategy for teacher development oriented toward quality, morality, and sustainability in Islamic education.